Boltzmann Machine Neural Network for Arabic Speech Recognition - Mohamed, H.R (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Boltzmann mach ine neural network bas been used to recognize the Arabic speech.  Fast Fourier transl(>lmation algorithm has been used t() extract speciral 'features from an a caustic signal .The  spectral  feature size is reduced by series of operations inorder to make it salable as input for a neural network which is used as a recogni zer by Boltzmann Machine Neural  network which has been used as a recognizer for phonemes . A training set consist of a number of Arabic phoneme repesentations, is used to train lhe neuntl network.The neural network recognized Arabic. After Boltzmann Machine Neura l    network   training  the  system   with   few  selected   Arabic phonemes, the results came out to be very encouragi ng .